Evaluation of wild grape germplasm for infestation of chaffer, beetle (Adoretus lasiophygus) - PATIL, S G; HONRAO, B K; KARKAMKAR, S P; DESHMUKH, M R (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1996-99 with 42 genotypes of wild grapes belonging to 5 genera of Vitaceae to evaluate the infestation of chaffer beetle (Adoretlls lasiophygus Burm,). of the 42 wild grapes, 5, viz Cissus hastata Mig., Cayratia trilobata Domin, Leea crispo Willd., Leea sambucina Willd. and Vitis parviflora Roxb., were found significantly resistant. Classification based on infestation showed 32 genotypes to be resistant, 6 tolerant and 4 moderately tolerant, None of the genotypes was observed moderately susceptible or susceptible.